Allochthonous arbuscular mycorrhizal fungi promote Salix viminalis L.–mediated phytoremediation of polycyclic aromatic hydrocarbons characterized by increasing the release of organic acids and enzymes in soils - Li, Xia; Kang, Xiaofei; Zou, Junzhu; Yin, Jiahui; Wang, Yuancheng; Li, Ao; Ma, Xiaodong (Ecotoxicology and environmental safety, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are well known persistent organic pollutants that have carcinogenic, teratogenic, and mutagenic effects on humans and animals. Arbuscular mycorrhizal fungi (AMF) that can infest plant hosts and form symbioses may help plants to enhance potential rhizosphere effects, thus contributing to the rhizodegradation of PAH-contaminated soils. The present study aimed to assess the effectiveness of AMF on enhancing Salix viminalis–mediated phytoremediation of PAH-polluted soil and clarify the plant enzymatic and organic acid mechanisms induced by AMF. Natural attenuation (NA), phytoremediation (P, Salix viminalis), S. viminalis-AMF combined remediation using willow inoculated with Funneliformis mosseae (PM), Laroideoglomus etunicatum (PE), and Rhizophagus intraradices (PI) were used as strategies for the remediation of PAH-polluted soils. The results showed that AMF inoculation contributed to the dissipation of the high-molecular-weight PAH benzo (α) pyrene that had concentrations in PM, PE, and PI treatments of 40.1 %, 24.49 %, and 36.28 % of the level in the NA treatment, and 62.32 %, 38.05 %, and 56.38 % of the level in the P treatment after 90 days. The mycorrhizal treatment also improved the removal efficiency of phenanthrene and pyrene, as their concentrations were sharply decreased after 30 days compared to the NA and P treatments. The research further clarified the changes in rhizosphere substances induced by AMF. Organic acids including arachidonic acid, octadecanedioic acid, α-linolenic acid, 10,12,14-octadecarachidonic acid and 5-methoxysalicylic acid that can act as co-metabolic substrates for certain microbial species to metabolize PAHs were significantly increased in AMF-inoculated treatments. AMF inoculation also elevated the levels of polyphenol oxidase, laccase, and dehydrogenase, that played crucial roles in PAHs biodegradation. These findings provide an effective strategy for using AMF-assisted S. viminalis to remediate PAH-polluted soils, and the results have confirmed the key roles of organic acids and soil enzymes in plant-AMF combined remediation of PAHs. [Display omitted] •Willow-AMF synergistically promoted the dissipation of soil HMW-PAHs.•Willow-AMF increased the contents of organic acids beneficial to metabolizing HMW-PAHs.•Willow-AMF elevated certain enzyme activities correlated with HMW-PAH degradation.